Do Scholars-Turned-Businessmen Impact Green Innovation? - Zhao, Jing; Li, Wanming; Zhang, Qian (Frontiers in Psychology, 2022)
This study explores how senior executives’ academic experience affects green innovation using Upper Echelons and Brand theories. Using a sample of China public companies and purposefully collected senior executives’ academic experience data, we propose that senior executives’ academic experience positively impacts green innovation. We also examine the moderating effects of management discretion factors (organizational slack, property rights nature, market competition degree). The results show that organizational slack positively moderates the relationship between senior executives’ academic experience and green innovation. Furthermore, the positive relationship between senior executives’ academic experience and green innovation is more significant in state-owned enterprises. Meanwhile, the degree of market competition negatively moderates the positive relationship between senior executives’ academic experience and green innovation. Improving comprehensive ability and environmental concern are two possible mechanisms through which the senior executives’ academic experience influences green innovation. The findings suggest that senior executives’ academic experience is an important factor for green innovation in emerging market firms.